POLITENESS STRATEGIES IN OFFICIAL FACEBOOK ACCOUNTS OF CNN, TWSJ AND NBC ON OBAMA VISITING HIROSHIMA - Rosyidah, Ima Fitriana; Sofwan, Ahmad (Universitas Negeri Semarang, 2017)
The purpose of this study was to identify and to count the percentage of the politeness strategies used in the comments of official facebook account of CNN, The Wall Street Journal, and NBC on Obama’s visit to Hiroshima. Then, it tried to find the politeness scale in the utterances of people toward Obama as the President of the United States at that time. Besides, it also tried to compare the politeness strategy that is often used in those three facebook accounts. In this study, the data analysis reveals research findings as follows: (1) there were positive politeness strategies used in the comments with the highest data was performed by the strategy 7 (presuppose) - 26.7%; and the lowest was performed by the strategy 3 (intensify interest) - 0.9%. Meanwhile, in the negative politeness strategy the highest data was performed by the strategy 7 (impersonalise speaker and hearer) - 55.7%; and the lowest was performed by the strategy 5 (give deference/humble oneself) - 0.7%, (2) the scale of politeness were determined by politeness factors, and the highest level was performed by the ranking of imposition, and (3) the politeness strategies and politeness scale mostly appeared in the NBC’s official facebook account.